Environmental Management of ISO 14001 System Enforcement in EU Countries - Zębek, Elżbieta Małgorzata (Review of European and Comparative Law, 2021)
The European Union International Organization for Standardization management system for the environment (ISO 14001) is established by European Commission Regulation 1221/2009. This legislates a voluntary system where organizations can register in a community eco-management and audit scheme. In the literature, this standard is recognized as an instrument of international environmental protection law, introduced by soft law regulations. ISO 14001 has been implemented by many global and European organizations, and it strives to improve the quality of their environmental resources. It was considered that the ISO 14001 eco-management and audit scheme enforced protection of environment in EU countries by imposing the obligation to implement appropriate legal regulations in this area. This article aims is determine what legal solutions in chosen UE countries enable the effective implementation of ISO 14001 and what positive effects it has on the state of the environment in these countries. The results demonstrated that the number of certified organizations is increasing despite the many difficulties and costs of implementing and organizing required environmental protection areas. The implementation of ISO 14001 was described using the example of Poland and Italy compared to other EU countries. The uptake identifies improved environmental quality, and this is confirmed by indicators of decreasing gas emissions and increasing waste recycling which improve global air, soil and water quality. The higher implementation index of the ISO 14001 standard in Italy translates into higher environmental quality indicators in this country than in Poland.